MANAGEMENT OF COVID-19 AND POST-COVID COMPLICATIONS - Xamidov Bobur A‘zam o‘g‘li; Utambetova Arzayim Kalmurzayevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The COVID-19 pandemic continues to pose significant long-term health challenges due to post-acute sequelae of SARS-CoV-2 infection, commonly known as Long COVID or post-COVID condition. This review provides a comprehensive overview of the current evidence on the management of acute COVID- 19 and its post-acute complications. It summarizes the pathophysiology, clinical manifestations across multiple organ systems, risk factors, diagnostic approaches, and evidence-based management strategies. A multidisciplinary, individualized approach combining rehabilitation, psychological support, and symptomatic treatment remains the cornerstone of care. Early vaccination, optimal acute-phase management, and timely rehabilitation are key to reducing the burden of Long COVID. Despite growing research, high-quality evidence for many therapeutic interventions is still limited, highlighting the need for continued research and specialized care pathways